2018
DOI: 10.1111/jfpp.13599
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intrinsic and extrinsic factors on moisture sorption characteristics of hard candy

Abstract: This study assessed effects of intrinsic factors, composition and candy size, and extrinsic factors, storage temperature, and humidity, on moisture sorption characteristics of hard candy. Nine types of plain hard candy with various percentage of sucrose (45.0 to 65.0% wt/wt) and citric acid (0.0 to 1.0% wt/wt) were prepared. The prepared samples had surface area per weight ratio (SA/W) of 2.05 to 3.69 cm2/g. Moisture sorption isotherms of all candy formulations were built at 25 °C and 35 °C and were well‐repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 18 publications
5
14
0
Order By: Relevance
“…According to Ergun et al (), the moisture content can vary from 3% to 5% in commercial products while the required shelf life is retained. A similar result was previously reported by Netramai et al (), who estimated that the critical moisture content of most products tested was <4% using adsorption isotherms. They reported that formulations with high sucrose content (65%) had a critical moisture content of approximately 5%.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…According to Ergun et al (), the moisture content can vary from 3% to 5% in commercial products while the required shelf life is retained. A similar result was previously reported by Netramai et al (), who estimated that the critical moisture content of most products tested was <4% using adsorption isotherms. They reported that formulations with high sucrose content (65%) had a critical moisture content of approximately 5%.…”
Section: Resultssupporting
confidence: 90%
“…A nonconstant range of residuals was observed across the plot of residuals versus predicted response values. A funnel-shaped pattern in this plot indicated the need for a transformation in the form of Equation (7) (Myers et al, 2016).…”
Section: Accelerated Shelf Life Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This behavior generally represents the sorption phenomena in biological materials, and is characterized by a J-shaped curve (Al-Muhtaseb et al, 2002). Similar results were obtained for confectionery products such as Turkish delight (Gögtüş et al, 1998), hard candies containing sorbitol and isomalt (Hadjikinova et al, 2003) and hard candies with sucrose and citric acid (Netramai et al, 2018).…”
Section: Resultssupporting
confidence: 75%
“…Citric acid is used as an antioxidant, a preservative and a taste coregent in hard candies at a concentration of 0–1% [ 54 ] and in gummy candies from 2.5% to 4.5% [ 55 ]. In this study, 0.96% citric acid concentration was not only used as a preservative for the chewable gel tablets but also to produce a better taste.…”
Section: Resultsmentioning
confidence: 99%